Institutionalising informal networks of the urban poor under an enabling paradigm: a case study on Greenland slum of Khulna city in Bangladesh. Issue 2 (3rd May 2020) - Rahman, Md. Ashiq Ur; Ley, Astrid
ABSTRACT: This paper addresses the persistent challenges in housing the urban poor in Bangladesh. In particular, it explores the empirical evidence on informal networks of the urban poor as they relate to service provision in low-income settlements of Khulna City. It also analyses the emerging forms of urban governance in low-income urban settlements. Specifically, it investigates the transformation process of project-assisted form of informal network of the urban poor. This paper argues that community-based organisations in poor settlements in Bangladesh represent informal networks of the urban poor. Whether these networks are being federated depends on their type or form, and this is often the outcome of project-led initiatives. The findings show that project based initiatives have failed to assist these networks with the appropriate rules and resources required for their effectiveness. Moreover, these efforts are taking place in a system that is attempting to establish enabling mechanisms under a system of neo-liberalism. Thus, it is necessary to explore the possible ways to bridge formal and informal processes through institutionalisation under a wider urban governance framework.